Phytochemical Screening of Sunflower Leaf (Helianthus annuus) and Anting-Anting (Acalypha indica Linn) Plant Ethanol Extract - Khoirul Ngibad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Many local plants in Indonesia were used as traditional medicines, such as sunflower (Helianthus annuus) and anting-anting (Acalypha indica Linn) plants. Both of them can be used as an antimalarial, antibacterial, antifungal, analgesic, and antihyperlipidemic. This study aims to provide an overview of the secondary metabolites groups contained in sunflower leaf and anting-anting plants for the testing of alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and sesquiterpenoids. This study included the extraction of sunflower leaves and anting-anting plants separately using the maceration method for 24 hours with 80% ethanol solvent. The stirring was aided by a shaker for three hours. Each extract was tested by phytochemicals with reagents. The results of phytochemical tests with reagents showed that 80% ethanol extract of sunflower leaves contained an alkaloid, tannin, steroid, and sesquiterpenoid compounds whereas anting-anting plants contained an alkaloid, flavonoid, and triterpenoid compounds.